2014
DOI: 10.1557/jmr.2014.317
|View full text |Cite
|
Sign up to set email alerts
|

In situ investigation of commercial Ni(OH)2and LaNi5-based electrodes by neutron powder diffraction

Abstract: Electrochemical reactions at both positive and negative electrodes in a nickel metal hydride (Ni-MH) battery during charge have been investigated by in situ neutron powder diffraction. Commercially available b-Ni(OH) 2 and LaNi 5 -based powders were used in this experiment as positive and negative electrodes, respectively. Exchange of hydrogen by deuterium for the b-Ni(OH) 2 electrode was achieved by ex situ cycling of the cell prior to in situ measurements. Neutron diffraction data collected in situ show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…As mentioned above, we have previously presented an in-situ electrochemical cell, figure 1 d), that was used for studies of both Ni(OD)2 and MmNi3.6Al0.4Mn0.3Co0.7 electrodes, where Mm refers to mischmetal, in a Ni-MH battery [22]. The results were interesting, since structural information obtained as a function of battery charge/discharge showed that the largest amount of deuterium contained at the positive electrode de-intercalates as a continuous solid solution, rather than by a phase transformation of the hexagonal Ni(OH)2 phase as commonly observed by ex-situ measurements.…”
Section: In-situ Electrochemical Cellsmentioning
confidence: 99%
“…As mentioned above, we have previously presented an in-situ electrochemical cell, figure 1 d), that was used for studies of both Ni(OD)2 and MmNi3.6Al0.4Mn0.3Co0.7 electrodes, where Mm refers to mischmetal, in a Ni-MH battery [22]. The results were interesting, since structural information obtained as a function of battery charge/discharge showed that the largest amount of deuterium contained at the positive electrode de-intercalates as a continuous solid solution, rather than by a phase transformation of the hexagonal Ni(OH)2 phase as commonly observed by ex-situ measurements.…”
Section: In-situ Electrochemical Cellsmentioning
confidence: 99%
“…The electrochemical cell originally constructed to conduct in-situ studies in a NiMH battery (Biendicho et al, 2014(Biendicho et al, , 2015, may be easily adapted to other energy storage systems due to its modular and flexible configuration. As presented in previous publications, the cell is based in a planar design stacking the components on top of each other, as in coin cells used in a laboratory to characterize electrode materials ex-situ.…”
Section: Resultsmentioning
confidence: 99%
“…However, the dimensions of the in-situ cell are significantly larger compared to standard coin cells to maximize the amount of electrode material exposed to the neutron beam; the outer cell diameter of the cell is 84 mm and usually accommodates rectangular-shaped electrodes of 1-2 g. Figures 1A,B show an expanded view of the in-situ cell and a sketch of the cell components and their position with respect to the incident neutron beam, respectively. Further details of the cell components and materials used to collect neutron diffraction patterns with an increased peak-to-background ratio may be found in previous publications (Roberts et al, 2013;Biendicho et al, 2014Biendicho et al, , 2015.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations